Major hydrological shifts in the Black Sea "Lake" in response to ice sheet collapses during MIS 6 (130–184 ka BP). (1st September 2019) - Wegwerth, Antje; Dellwig, Olaf; Wulf, Sabine; Plessen, Birgit; Kleinhanns, Ilka C.; Nowaczyk, Norbert R.; Jiabo, Liu; Arz, Helge W.
Abstract: The Saalian was one of the largest glaciations during the Quaternary with an ice sheet extending considerably wider into the Eurasian continent than during other glacials. Orbital variations caused the ice sheet to switch between growing and shrinking. The partial retreat of the ice sheet and meltwater discharge resulted in global sea-level rise and increased lake levels of inland seas with broader environmental implications. During Marine Isotope Stage 6 (MIS 6), meltwater entered the formerly enclosed Black Sea at least twice as documented in a δ 18 O record from Anatolian speleothems. Here we present a sedimentary record from the Black Sea "Lake" covering MIS 6 and provide evidence for three meltwater periods coinciding with insolation maxima (BSWP-6-1: 180-167 ka BP, BSWP-6-2: 160-145 ka BP, BSWP-II: 133-130 ka BP). While δ 18 Oostracods and Sr/Caostracods point to pronounced meltwater supply and decreasing salinity, 87 Sr/ 86 Srostracods shed light on meltwater sources and pathways. During all three periods, meltwater drained most likely via the Dnieper and Volga into the Black and Caspian Seas and connected both basins. Relatively low 87 Sr/ 86 Srostracods values during the oldest meltwater period suggest melting solely of the eastern Eurasian Ice Sheet. In contrast, during the younger meltwater periods, exceptional high 87 Sr/ 86 Srostracods values point towards additional meltwater from the western Eurasian Ice Sheet. A surplus from melting glaciers in the Tian Shan and Pamir Mountains that finally entered the Caspian Sea via the Amu Darya and Sry Darya probably amplified the input of high radiogenic Sr-isotope water. We also show that higher temperatures and productivity suggest Dansgaard-Oeschger-like climate variability during the first half of MIS 6. Highlights: Black Sea "Lake" record between 184 ka BP and 124 ka BP (MIS 6-5e) is presented. Main parameters are δ 18 O, 87 Sr/ 86 Sr, Sr/Ca, and Mg/Ca of ostracods. Higher temperatures and stadial-interstadial variability during early MIS 6. Three long-term meltwater periods during insolation maxima and retreated ice sheets. Caspian–Black Sea connection during meltwater periods, but different sources/pathways.